The Role of Mediators in the Resolution of Joint Property Disputes: A Meta-Analysis and Systematic Review - Oman Sudrajat (PT. Ratu Bilqis Azzahira bekerjasama dengan Fakultas Syariah Universitas Islam Zainul Hasan Probolinggo, 2025)
Joint property disputes following divorce are among the most complex and emotionally charged issues in family law. Mediation has emerged as a preferred alternative dispute resolution (ADR) method, particularly in Muslim-majority societies, where legal processes are often shaped by both state law and Islamic principles. This study aims to systematically evaluate the role of mediators in resolving joint property disputes by conducting a meta-analysis and systematic review based on the PRISMA 2020 methodology. Twenty peer-reviewed studies published between 2018 and 2024 were analyzed from databases such as Scopus, ScienceDirect, PubMed, and Mendeley. The findings indicate that effective mediation is characterized by mediator neutrality, cultural and religious competence, gender sensitivity, and a clear understanding of both legal and ethical frameworks. Mediators who integrate Islamic values such as justice (ʿadl), reconciliation (islāh), and public benefit (maslahah) were more successful in achieving durable and equitable outcomes. However, the study also identifies critical challenges, including inconsistent training standards, gender bias, and institutional gaps in supporting mediation practices. This review concludes that mediation, when professionally implemented and ethically grounded, offers a powerful and contextually relevant tool for promoting fair and sustainable resolutions to joint property disputes in post-divorce settings